Game Design for Eysenck Method Personality Test Using Unity - Liniarto, Edbert; Nugroho, Erdhi Widyarto; Nugroho, Agus Cahyo (Journal of Business and Technology, 2024)
In this day and age, there continues to be a growth in technology that makes things easier and more effective. In addition, the distance that was originally a major problem for connecting, talking, exchanging thoughts or data with others disappeared because of the globalization that occurred. The growth of science and technology is basically a growth that aims to achieve and fulfill human aspirations and needs in using resources. Therefore, the idea arose to design a simple personality test game.The purpose of this research is to design a windows10 operating system-based game into the "Personality Test" game. Questions from the Eysenck test will be made into the game. This game will be implemented into the game using unity. The method used in research is to collect data by interviewing users to get data quickly.